DEVELOPING PRAGMATIC COMPETENCE AS A SUBCOMPONENT OF COMMUNICATIVE COMPETENCE IN FOREIGN LANGUAGE TEACHING (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
In contemporary foreign language pedagogy, communicative competence is regarded as the ultimate goal of instruction. Among its subcomponents, pragmatic competence plays a central role in enabling learners to use language appropriately in diverse social and cultural contexts. Despite its importance, pragmatic competence often remains underdeveloped in foreign language classrooms, where grammatical accuracy is frequently prioritized over contextual appropriateness. This paper provides a comprehensive analysis of pragmatic competence as a subcomponent of communicative competence, explores its internal structure, identifies challenges in its development, and proposes pedagogical strategies for its effective integration into language teaching. The study argues that explicit instruction, authentic input, and intercultural awareness are essential for fostering pragmatic competence in learners.